2019
DOI: 10.32674/jis.v9i1.273
|View full text |Cite
|
Sign up to set email alerts
|

Studying in the United States: Language Learning Challenges, Strategies and Support Services

Abstract: A case study was conducted to explore the experiences of Chinese nurses when completing a graduate nursing degree taught in English (as a second language) in the United States over a one-year period. The study explored language, academic, and social challenges perceived by the students, strategies used to overcome challenges, and academic support services designed to help students succeed in their studies. Survey data were collected at three different points in time, and three interviews were conducted with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…The problems international students face in the United States are commonly summarized as "adapting to a new culture, English language problems, financial problems and lack of understanding from the broader university community" (Sherry et al, 2010, p. 33). This has led to recommendations for pedagogical development of the staff in receiving institutions (Wolf & Phung, 2019). However, Lee and Rice (2007) have pointed out that not all problems international students face can and should be understood as matters of individual adjustment.…”
Section: The Paradox Of High Language Skills and Am Coursesmentioning
confidence: 99%
“…The problems international students face in the United States are commonly summarized as "adapting to a new culture, English language problems, financial problems and lack of understanding from the broader university community" (Sherry et al, 2010, p. 33). This has led to recommendations for pedagogical development of the staff in receiving institutions (Wolf & Phung, 2019). However, Lee and Rice (2007) have pointed out that not all problems international students face can and should be understood as matters of individual adjustment.…”
Section: The Paradox Of High Language Skills and Am Coursesmentioning
confidence: 99%
“…Research demonstrated that ELs with limited English proficiency experienced increased levels of academic stress, negative well-being, and feelings of social isolation. For example, in their case study of eight Chinese international graduate students in nursing, Wolf and Phung (2019) found that ELs experienced difficulties with academic writing and reported mixed challenges with speaking in classroom interactions. Likewise, Luo and colleagues (2019) conducted a survey study of 216 mostly undergraduate international students, primarily from East Asian countries, ranging from 17 to 38 years of age.…”
Section: Literature Review Academic Challenges and Stressorsmentioning
confidence: 99%
“…For example, many ELs lack cognitive academic language proficiency (CALP) needed for university-level coursework (Andrade, 2009). Furthermore, because of deficient language skills, ELs often delay participating in discussions and feel overwhelmed or alienated while in class (Andrade, 2009;Wolf & Phung, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If sense of belonging and connection leads to success, what leads to belonging and connection? A survey of the literature suggests that when international students feel supported, they are more likely to feel socially connected (Encinas & Ammigan, 2016;Tchoh & Mertan, 2018;Wolf & Phung, 2019). García et al (2019) found, for example, that international students who are more socioacademically integrated tend to graduate and be retained at higher rates in community colleges.…”
Section: Supportmentioning
confidence: 99%